Networked teacher professional development: Sharing and learning using social networking tools - Ostashewski, Nathaniel; Reid, D. (AACE, 2012)
This paper articulates the advancement of a new model of teacher professional development (TPD) that integrates social networking concepts into professional learning situations. This model is called Networked Teacher Professional Development (nTPD) and expands upon online professional development for teachers (oTPD). Key attributes of nTPD include a learning space that is persistent over time, utilization of social networking tools, and a focus on teacher discourse about pedagogy and teaching resources. An important part of the development of the nTPD model was the creation of a structure of successful learning activities in a variety of content areas. Teachers report that the sharing of resources, collegial discussions, and course resources are valuable in supporting and expanding their teaching practice. Online tool experience in a professional environment was reported by teachers to have a positive impact on their professional practice. More research on supporting further teacher connections in nTPD implementations is needed.